(untitled) (Research, Society and Development, 2021)
Euterpe oleracea Mart. is a palm tree native to the Amazon, popularly known as açaizeiro. This species has great economic importance in the region, influencing and moving its large markets. Its cultivation is aimed at the production of fruits and hearts of palm. Açaí in recent years has been consumed on a large scale in several regions of Brazil and has been consolidating in national and international markets. With the growth of this market, there was also an increase in interest in the production of quality seedlings in order to meet this demand. Thus, it aimed to evaluate the use of different substrate compositions in the development of açaí seedlings. The experiment was conducted in a greenhouse with 50% shading located in the UFG, with a completely randomized design with 3 treatments and 6 replications. The substrates used were: T1 – EMBRAPA Standard: 20% manure + 20% sawdust + 60% soil; T2 – 20% sand + 20% manure + 60% commercial substrate; and T3 – 20% sand + 20% manure + 20% soil. Data were obtained from: seedling height, stem diameter, number of leaves, fresh and dry matter mass and relative chlorophyll index. Analyzes were performed on the substrates to determine density, water holding capacity, pH and electrical conductivity. It was found that the substrates showed similar results, allowing the use of any of them, according to the ease of obtaining.